Treatment of Striae Distensae with Filler Injection: A Systematic Review - Alsharif SH; Alghamdi AS; Alhumaidi WA; AlRobaish OA; Al Hamoud MH; Alruwaili AS; AlQefari GB; Almutairi RT (Dove Medical Press, 2023)
Sahar Hasan Alsharif,1,* Asail Saeed Alghamdi,2,* Wareef Abdulkarim Alhumaidi,3 Omar Abdulaziz AlRobaish,4 Mohammad Hassan Al Hamoud,5 Asma Saleh Alruwaili,6 Ghaida B AlQefari,7 Rahaf Tayi Almutairi8 1Department of Dermatology, Ministry of Health, Makkah, Saudi Arabia; 2Department of Medicine, Albaha University, Albaha, Saudi Arabia; 3Department of Medicine, Taif University, Taif, Saudi Arabia; 4Department of Dermatology, King Fahad Specialist Hospital, Buraidah, Saudi Arabia; 5Department of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 6Department of Medicine, Northern Border University, Arar, Saudi Arabia; 7Department of Medicine and Surgery, Qassim University, Qassim, Saudi Arabia; 8Department of Medicine, King Faisal University, Al Ahsaa, Saudi Arabia*These authors contributed equally to this workCorrespondence: Sahar Hasan Alsharif, Department of Dermatology, Ministry of Health, Makkah, Saudi Arabia, Tel +966555539141, Email S.H.Alsharif@hotmail.comBackground: Stretch marks, also known as striae cutis distensae (SD), are visible linear scars that occur in regions of dermal damage due to skin stretching. Stretch marks are not serious health issues, but they may have a major psychological effect on patients. Due to poor skin color improvement or prolonged skin atrophy, there is no standard treatment for SD. Fillers have been studied for their effectiveness in the treatment of SD.Objective: This systematic review aims to determine the efficacy of fillers on SD.Methods: This systematic review is reported following PRISMA guidance. We included all relevant articles published up to November 2022 in the following electronic databases: Science Direct, Midline, the Web of Science, CINAHL, and Google Scholar. The initial search yielded 119, of which seven were included after applying inclusion and exclusion criteria.Results: The systematic review included a total of 184 female participants who were over the age of 18 years old. Three studies used jet volumetric remodeling (JVR) to inject HA pneumatically. One study injected polycaprolactone filler. One study used calcium hydroxylapatite, micro-needling, and ascorbic acid. MFU-V and CaHA were given in one study. One study delivered MFU-V using micro-focused ultrasound. All studies showed that it reduces SD with only mild, temporary side effects. More favor was given to combining CaHA and MFU-V, which had the fewest side effects compared to other dermal fillers.Conclusion: As monotherapy or combination therapy, injectable dermal fillers may treat SD with minimal adverse effects. We suggest that more RCTs look into injectable dermal filler to find out what is best for patients with SD and compare it to other treatment methods in terms of results, costs, and side effects to provide satisfactory practice and basic guideline interventions for these cases.Keywords: striae distensae, Fillers, SD, Efficacy